Application Of Data Mining For Classification Of BLT-DD Recipients Using The Support Vector Machine Method - Meliza Putri; Bustami; Ar Razi (Faculty of Engineering, Malikussaleh University, 2024)
This study focuses on the application of the Support Vector Machine (SVM) algorithm for classifying recipients who are eligible to receive Direct Cash Assistance from the Village Fund (BLT-DD) in Nurussalam District, East Aceh Regency. The background of this research is the difficulty in identifying households eligible for BLT-DD due to increasing poverty and economic inequality exacerbated by the COVID-19 pandemic. This study aims to address this issue by utilizing the SVM algorithm, which can separate household data into two categories: